2022
DOI: 10.25259/sni_483_2022
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-induced encephalopathy in a patient with multicentric glioma

Abstract: Background: Ceftriaxone is a commonly used antibiotic in a wide range of local and systemic infections. Encephalopathy is a rare complication of ceftriaxone, often seen in older adults and those with renal insufficiency. Case Description: A 73-year-old lady with prior history of hypertension and dyslipidemia presented with the complaints of slurred speech, gait imbalance, nocturnal vomiting, and progressively worsening headache. A magnetic resonance imaging of the brain revealed two intracerebral lesions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We did a literature review on PubMed in April 2023 without a time limit and identified 15 case reports,4 6–9 11–13 15–18 20 21 26 7 small case series2 3 5 10 14 19 27 and 2 pharmacovigilance database analysis22 28 discussing serious neurological effects of ceftriaxone in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did a literature review on PubMed in April 2023 without a time limit and identified 15 case reports,4 6–9 11–13 15–18 20 21 26 7 small case series2 3 5 10 14 19 27 and 2 pharmacovigilance database analysis22 28 discussing serious neurological effects of ceftriaxone in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Please note that we decided to exclude one case report because of possible confounding factors not detailed in the report 26 and one case series because of radically different patient descriptions in the written text and the supplied chart. 27 …”
Section: Discussionmentioning
confidence: 99%